TAXONOMIC IDENTIFICATION OF DIATOMS IN VARUNA RIVER: A TOOL FOR FORENSIC INVESTIGATIONS - Verma, Siddharth; Singh, Rajiv Ratan; Tripathi, Sachin Kumar; Gupta, Sanjay; Yadav, Pradeep Kumar (Journal of Forensic Medicine and Toxicology, 2025)
Introduction: Exploring the taxonomic diversity of diatoms in the Varuna River unveils a fascinating realm with profound implications for forensic investigations. The intricate ecological web of these microscopic organisms offers a unique lens to scrutinize environmental dynamics, providing valuable insights crucial in forensic science for accurate analysis and interpretation. Aim: This study aims to analyze diatom populations in the Varuna River across Varanasi, Prayagraj, Bhadohi, and Jaunpur, focusing on their identification, quantification, distribution, and forensic relevance in drowning cases. Methodology: This qualitative experimental study investigates Diatom species variation along the Varuna River, collecting thirteen samples strategically across its 202-kilometer length in Uttar Pradesh, India. The comprehensive approach includes Plankton net collection, immediate preservation with 4% Formaldehyde, meticulous laboratory analysis, and TILIA software for range charts and CONISS cluster analysis. Results: Twenty-three diatom genera were identified, with pennate diatoms being predominant (90%) compared to centric diatoms (10%), except for one site. Ten genera were common across multiple sites, while 11 were site specific. Diatom clustering revealed three distinct zones along the river, each exhibiting unique diatom compositions reflecting varying environmental conditions which could aid forensic investigation in drowning cases. Conclusion: The study underscores the diversity and specificity of diatom populations within the Varuna River, indicating potential variations in environmental conditions across sites. The identification of specific diatom markers holds promise for forensic applications, potentially linking individuals or suspects to particular locations in case of anti-mortem and post-mortem drowning or dead body dumping cases.
Keywords: Bioindicator; Crime scene analysis; Diatom Profiling; Drowning cases; Forensic diatomology; Varuna River